2012
DOI: 10.1136/annrheumdis-2012-201404
|View full text |Cite
|
Sign up to set email alerts
|

Differential synovial Th1 cell reactivity towardsEscherichia coliantigens in patients with ankylosing spondylitis and rheumatoid arthritis

Abstract: The high frequency and enrichment of E coli-specific CD4 T cells in the inflamed joints of patients with AS but not those with RA suggests that commensal bacteria are relevant antigens in AS that might trigger the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Similarly, P. gingivalis was shown to be the potential initiator, causing RA to form ACPAs [84]. Recent studies have shown a close relationship between microbiota and RA, including Mycoplasma [86] , Proteus [87], Escherichia [88], Haemophilusspp, Lactobacillussalivarius , etc. [89].…”
Section: Effects Of Gut Microbiome and Mucosal Immunity In Autoimmunementioning
confidence: 99%
“…Similarly, P. gingivalis was shown to be the potential initiator, causing RA to form ACPAs [84]. Recent studies have shown a close relationship between microbiota and RA, including Mycoplasma [86] , Proteus [87], Escherichia [88], Haemophilusspp, Lactobacillussalivarius , etc. [89].…”
Section: Effects Of Gut Microbiome and Mucosal Immunity In Autoimmunementioning
confidence: 99%
“…found that the E. coli-specific Th1 response was significantly reduced in Crohn’s patients and to a lower extent also in AS patients ( 32 ), and Syrbe et al. found that the high frequency and enrichment of E coli-specific CD4 T cells in the inflamed joints of patients with AS ( 33 ), which suggested that the “Pathogenic Escherichia coli infection” might be relevant to AS. For the “Pathogenic Escherichia coli infection” pathway, the study recognized some important inflammatory factors, such as TNF-α, IL‐1β, IL‐1, IL‐8, and NF‐κb, which were associated with different signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Environmental factors such as Escherichia coli have also been proven to aggravate autoimmunity in AS and NMOSD (however, body fluid cultures for Escherichia coli , performed in our patient, showed similar association, and they were found negative two times). 21 , 22 Although large-scale epidemiological studies investigating the underlying pathogenesis related to these diseases are lacking, studies have demonstrated an increased incidence of optic neuritis among patients with AS. 23 Systemic sclerosis and mixed and undifferentiated connective tissue diseases were excluded after expert opinions (from two board-certified rheumatologists and two dermatologists) because of the lack of suggestive clinical findings (e.g., absence of skin thickening, salt-and-pepper appearance, nail changes, Mauskopf facies, sclerodactyly, calcinosis cutis, Raynaud’s phenomenon, other cutaneous manifestations, pulmonary arterial hypertension/interstitial lung disease, dysphagia, muscular pain/weakness renal impairments, absence of ANA, anti-centromere antibodies, anti-Scl-70, PM-Scl antibodies, anti-ds DNA, PCNA, CENP-B, anti-nucleosomes, anti-Smith, anti-U1-RNP, anti-Jo1, anti-Mi2, anti-Ro52, anti-La antibodies, and normal C3 and C4 complement levels) (The European League Against Rheumatism and the American College of Rheumatology classification criteria 2019).…”
mentioning
confidence: 99%
“… 20 Environmental factors such as Escherichia coli have also been proven to aggravate autoimmunity in AS and NMOSD (however, body fluid cultures for Escherichia coli , performed in our patient, showed similar association, and they were found negative two times). 21 , 22 Although large-scale epidemiological studies investigating the underlying pathogenesis related to these diseases are lacking, studies have demonstrated an increased incidence of optic neuritis among patients with AS. 23 …”
mentioning
confidence: 99%